FUNDAMENTAL ANALYSIS TECHNIC AND STOCK PRICE - Sofia Ulfa Eka Hadiyanti; Praja Hadi Saputra (Jurnal Ekonomi dan Manajemen, 2020)
This study aims to determine the effect of Price Earning Ratio, Earning Per Share, Book Value Ratio Price, Debt to Equity Ratio, and Net Profit Margin on stock prices in the hotel, restaurant, and tourism sub sector issuers in 2017 for 12 months. The sampling technique uses purposive sampling method, with the number of samples used in this study as many as 9 companies. The variables used in this study are Price Earning Ratio, Earning Per Share, Price Book Value Ratio, Debt to Equity Ratio, and Net Profit Margin as independent variables. The stock price is the dependent variable. The statistical testing method used in this study is multiple linear regression analysis. And hypothesis testing uses the F test to test the effect of simultaneous variables and the T test to test the coefficient partially at a significant level of 5%. Besides that, it also used data normality test, classic assumption test which included autocorrelation test, multicollinearity test, and heteroscedasticity test. The results of the analysis using multiple regression indicate that: Price Earning Ratio, Price Book Value, and Net Profit Margin have a positive effect on Stock Prices, while Earning Per Share and Debt to Equity Ratio negatively affect Stock Prices.